Mothers matter too: benefits of temperature oviposition preferences in newts - Kurdíková, Vendula; Smolinský, Radovan; Gvoždík, Lumír (PloS one, 2011)
The maternal manipulation hypothesis states that ectothermic females modify thermal conditions during embryonic development to benefit their offspring (anticipatory maternal effect). However, the recent theory suggests that the ultimate currency of an adaptive maternal effect is female fitness that can be maximized also by decreasing mean fitness of individual offspring. We evaluated benefits of temperature oviposition preferences in Alpine newts (Ichthyosaura [formerly Triturus] alpestris) by comparing the thermal sensitivity of maternal and offspring traits across a range of preferred oviposition temperatures (12, 17, and 22°C) and by manipulating the egg-predation risk during oviposition in a laboratory thermal gradient (12-22°C). All traits showed varying responses to oviposition temperatures. Embryonic developmental rates increased with oviposition temperature, whereas hatchling size and swimming capacity showed the opposite pattern. Maternal oviposition and egg-predation rates were highest at the intermediate temperature. In the thermal gradient, females oviposited at the same temperature despite the presence of caged egg-predators, water beetles (Agabus bipustulatus). We conclude that female newts prefer a particular temperature for egg-deposition to maximize their oviposition performance rather than offspring fitness. The evolution of advanced reproductive modes, such as prolonged egg-retention and viviparity, may require, among others, the transition from selfish temperature preferences for ovipositon to the anticipatory maternal effect.
Keywords: Animals; Salamandridae; Mothers; Oviposition; rozmnožování; kladení vajíček; Body Temperature; ženské pohlaví; zvířata; tělesná teplota; Reproduction; Female; matky